1967
DOI: 10.1126/science.156.3773.408
|View full text |Cite
|
Sign up to set email alerts
|

Permanence of Retrograde Amnesia Produced by Electroconvulsive Shock

Abstract: The permanence of retrograde amnesia produced for a single training trial by a single electroconvulsive shock was studied. No recovery from amnesia was found with either single or repeated retention tests. Amnesic effects were found to be permanent with retention intervals as long as 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
42
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 9 publications
7
42
0
Order By: Relevance
“…Experimental procedures usually include a singletrial avoidance task followed by amnestic treatments (e.g., electroconvulsive shock) at various intervals after training. Results from early experiments revealed that memories were susceptible to being disrupted within 1 to 3 hours after training (depending on shock intensity), and would not be affected if treatments were administered outside this window (McGaugh, 1966;Luttges & McGaugh, 1967).…”
mentioning
confidence: 99%
“…Experimental procedures usually include a singletrial avoidance task followed by amnestic treatments (e.g., electroconvulsive shock) at various intervals after training. Results from early experiments revealed that memories were susceptible to being disrupted within 1 to 3 hours after training (depending on shock intensity), and would not be affected if treatments were administered outside this window (McGaugh, 1966;Luttges & McGaugh, 1967).…”
mentioning
confidence: 99%
“…Zinkin & Miller (1967) found that in a step-down apparatus with rats, recovery from amnesia observed at 24 h occurred if the animals were given additional reinforced trials at 48 and 72 h. Luttges & McGaugh (1967) found this not to be true for mice using a step-through apparatus.…”
mentioning
confidence: 99%
“…As explained traditionally by the concept of memory consolidation, RA results from a failure of memory storage (see, e.g., Jacobs & Sorenson, 1969;Riccio, Hodges, & Randall, 1968;Spanis & Squire, 1987), and it has been thought by many researchers to be permanent (e.g., King & Glasser, 1970;Luttges & McGaugh, 1967). However, increasing numbers of studies continue to demonstrate that animals are able to recover memories thought to be lost permanently due to the amnesic treatment (see Riccio & Richardson , 1984, for a review).…”
Section: Hypothermia-induced Retrograde Amnesia In Young and Adult Swmentioning
confidence: 99%